CRIMINAL ACTS IN THE FIELD OF SCIENCE AND TECHNOLOGY - Wijaya, Rudi; Raharjo, Eko; Agustina, Maria (Sriwijaya Crimen and Legal Studies, 2023)
Law Number 11 of 2019 on the National System of Science and Technology (UU Sisnas Iptek) is a law that is fundamental in the field of science and technology as well as monumental because it replaces Law Number 18 of 2002 on the National System for Research, Development, and Application of Science Knowledge and Technology that has been valid for 17 (seventeen) years amid very dynamic and unstoppable developments in science and technology. The replacement of the law contains consequences for changes in content material, including regulations regarding criminal acts regulated therein. The National System and Technology Law provides arrangements regarding criminal sanctions. It also regulates actions that are classified as criminal offenses. This research uses normative legal research methods and legal comparison methods with a statute approach. This article intends to describe the development of the regulation of sanctions and analyze the construction of criminal acts and the sanctions that surround them as regulated in the Science and Technology National System Law and the laws that were previously in effect. Based on the research conducted, it can be concluded that there has been a development of criminal acts in the field of science and technology, namely the addition of types of offenses, additional types of additional punishments, and ballast punishments. This development is a change for the better because it provides clarity and certainty for dangerous and potentially harmful actions.